Prescription Pattern In Hypertensive Patients In A Tertiary Care Teaching Hospital, Dhaka, Bangladesh - Roy, Udoy Shankar; Khandaker, Nazibur Rahman; Uddin, Saleh; Khan, Murshidur Rahman; Sarker, Nihar Ranjan (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Irrational drug prescribing is a common practice globally; it results in increased morbidity, mortality & economic burden on society. Drug utilization studies are an important tool to promote rational prescribing. Aims & Objective: To study on drug prescribing pattern in hypertensive patients. Materials and Methods: A drug utilization study was conducted in hypertensive patients by the department of cardiology in OPD at Shaheed Suhrawardy Medical college hospital for 6 months. 645 prescriptions were evaluated for prescribing pattern by using WHO drug use indicators. Results: 645 prescriptions were analyzed. A total of 1828 drugs were prescribed. 697 (38.13%) antihypertensive, 243 (13.30%) anti diabetics, 174 (9.52%) non-steroidal anti-inflammatory drugs (NSAIDs), 154 (8.44%) statins, 114 (6.24%) thyroid hormone, 54 (2.95%) anti-anxiety/ antidepressants and 392(21.44%) miscellaneous drugs were prescribed. 697 antihypertensive drugs were prescribed. 234 (33.57%) angiotensin receptor blockers (ARBs), 117 (16.79%) angiotensin converting enzyme (ACE) inhibitors, 95 (13.63%) Beta blockers, 83 (11.91%) Calcium channel blockers 168 (24.10%) Fixed dose combinations (FDCs) of antihypertensive were included. 2.83 drugs were prescribed per prescription. 225 (32.28%) antihypertensive were prescribed from essential medicine list. Conclusion: Most commonly prescribed drugs were ARBs and ACE inhibitors. Rational prescribing requires consideration to dose and duration and interaction with other medications. J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 39-43